A Thermodynamic Framework for Stretching Processes in Fiber Materials - Arango-Restrepo, A.; Rubi, J. M.; Pradhan, Srutarshi (Frontiers in Physics, 2021)
Fiber breakage process involves heat exchange with the medium and energy dissipation in the form of heat, sound, and light, among others. A purely mechanical treatment is therefore in general not enough to provide a complete description of the process. We have proposed a thermodynamic framework which allows us to identify new alarming signals before the breaking of the whole set of fibers. The occurrence of a maximum of the reversible heat, a minimum of the derivative of the dissipated energy, or a minimum in the stretching velocity as a function of the stretch can prevent us from an imminent breakage of the fibers which depends on the nature of the fiber material and on the load applied. The proposed conceptual framework can be used to analyze how dissipation and thermal fluctuations affect the stretching process of fibers in systems as diverse as single-molecules, textile and muscular fibers, and composite materials.